DE LA ‘VERDAD HISTÓRICA’ A LA ‘VEROSIMILITUD NARRATIVA’ DEL TERROR: LA FIESTA DEL CHIVO (VARGAS LLOSA) - HAIDAR, JULIETA (Revista Alere, 2015)
Vargas Llosa’s novel, La fiesta del chivo, focuses on the ever complex relationship between reality and literature. In this work, the fictional and the historical are interwoven in a decisive way. Such a fragile bounf finds one of his supporters in the very development of Latin America and the Caribbean, once the real history often seems to belong and to overcome the fictional world. The work in question makes us rethink the problems concerning the typology of genres, the historical memory, the mnemonic processes, the taboos in the construction of the historical and political memory of the trujillismo